DENIED CURIOSITY: WHEN NEGLECTED CHILDHOOD FAVORS THE RISK OF SEXUAL ABUSE - Fernandes Ledo Neto, Artur Augusto [UNESP]; Jacinto, Jessica Costa [UNESP]; Desiderio, Ricardo [UNESP] (Unesp-faculdade Ciencias & Letras, 2020)
For this work, we adopted the analysis methodology based on a bibliography on child sexual abuse, a theme that contains within itself the ambivalence of being taboo and urgent. Taboo, for being prohibited and surrounded by secrets, discrimination, prejudice and urgent, since it is necessary to provide adequate spaces, ethical and scientifically supported, given the growing and accentuated occurrence of this mode of rape and violence against children. We aim to analyze the importance of Child Sexual Education, so that its work in school education is combined with a legitimate and socially responsible device(4) as a contribution to the fight against child sexual abuse.
Keywords: Education; Sexuality; Childhood; Violence; Coping